2019
DOI: 10.1093/intbio/zyz003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid translocation of pluripotency-related transcription factors by external uniaxial forces

Abstract: Human embryonic stem cells subjected to a one-time uniaxial stretch for as short as 30-min on a flexible substrate coated with Matrigel experienced rapid and irreversible nuclear-to-cytoplasmic translocation of NANOG and OCT4, but not Sox2. Translocations were directed by intracellular transmission of biophysical signals from cell surface integrins to nuclear CRM1 and were independent of exogenous soluble factors. On E-CADHERIN-coated substrates, presumably with minimal integrin engagement, mechanical strain-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Following 3D differentiation, we observed a shift in the subcellular localization of Nanog and OCT3/4. Consistent with previous reports, Nanog, a mechanosensitive factor, undergoes translocation during the transition from cell renewal to differentiation ( Gu et al, 2012 ; Topal et al, 2019 ). Given the continuous movement inherent in our 3D model, we speculate that a similar phenomenon may be occurring in our system.…”
Section: Discussionsupporting
confidence: 92%
“…Following 3D differentiation, we observed a shift in the subcellular localization of Nanog and OCT3/4. Consistent with previous reports, Nanog, a mechanosensitive factor, undergoes translocation during the transition from cell renewal to differentiation ( Gu et al, 2012 ; Topal et al, 2019 ). Given the continuous movement inherent in our 3D model, we speculate that a similar phenomenon may be occurring in our system.…”
Section: Discussionsupporting
confidence: 92%
“…The subcellular localization analysis of pluripotency factor protein expression showed that NANOG and SOX2 were expressed in the nucleus and cytosol of human mesothelioma and Mero-14 cells. Topal et al showed that increased flux of OCT4 and NANOG, but not SOX2, from the nucleus into cytosol is associated with their degradation and differentiation of stem cells [ 34 ]. Thus, our observation that NANOG is present in the nucleus of mesothelioma, further corroborates that differentiation processes are inhibited in mesothelioma, rendering mesothelioma a highly undifferentiated cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage over the time-consuming western blot [ 40 ], is that immunocytochemical quantification is not prone to error due to protein crosslinking [ 41 ], it allows cell visualization and analysis of cell subpopulations, protein quantification in subcellular compartments and high-throughput experimentation when working with cell culture. This is important when studying SOX2 and NANOG expression, because their subcellular localization can determine the cell fate [ 34 ]. However, such quantification of protein expression in tissue slides does not always allow such approach due to the existence of multiple cell layers.…”
Section: Discussionmentioning
confidence: 99%